Porphyromonas endodontalis HmuY differentially participates in heme acquisition compared to the Porphyromonas gingivalis and Tannerella forsythia hemophore-like proteins - Śmiga, Michał; Olczak, Teresa (Frontiers in Cellular and Infection Microbiology, 2024)
Porphyromonas gingivalis and Porphyromonas endodontalis belong to the Bacteroidota phylum. Both species inhabit the oral cavity and can be associated with periodontal diseases. To survive, they must uptake heme from the host as an iron and protoporphyrin IX source.Among the best-characterized heme acquisition systems identified in members of the Bacteroidota phylum is the P. gingivalis Hmu system, with a leading role played by the hemophore-like HmuY (HmuY Pg ) protein.Methods: Theoretical analysis of selected HmuY proteins and spectrophotometric methods were employed to determine the heme-binding mode of the P. endodontalis HmuY homolog (HmuY Pe ) and its ability to sequester heme. Growth phenotype and gene expression analysis of P. endodontalis were employed to reveal the importance of the HmuY Pe and Hmu system for this bacterium.Results: Unlike in P. gingivalis, where HmuY Pg uses two histidines for heme-iron coordination, other known HmuY homologs use two methionines in this process. P. endodontalis HmuY Pe is the first characterized representative of the HmuY family that binds heme using a histidine-methionine pair. It allows HmuY Pe to sequester heme directly from serum albumin and Tannerella forsythia HmuY Tf , the HmuY homolog which uses two methionines for heme-iron coordination. In contrast to HmuY Pg , which sequesters heme directly from methemoglobin, HmuY Pe may bind heme only after the proteolytic digestion of hemoglobin.We hypothesize that differences in components of the Hmu system and structurebased properties of HmuY proteins may evolved allowing different adaptations of Porphyromonas species to the changing host environment. This may add to the superior virulence potential of P. gingivalis over other members of the Bacteroidota phylum.